ANALISIS KUALITATIF DAN KUANTITATIF FORMALDEHID PADA IKAN ASIN DI MADURA - Sri Hastuti (AGROINTEK, 2010)
The objective of the study is to know the content of formaldehid of salted fish which taken from tradisional market in Bangkalan and Sampang. The experiment conducted at the Laboratory of Agroindustry Technology, Faculty of Agriculture, Trunojoyo University Madura on June 2010. This research uses reagent chromotophic acid (C10H6Na2O8S2.2H2O). The test is positive indicated by the red through the purple color. The process continued by spectrophotometer. The result of the research shows that all samples from Kamal, Socah, Bangkalan and Sampang markets contain formaldehid i.e: 29,10 mg/kg, 30,65 mg/kg, 49,26mg/kg, 44,14 mg/kg respectively.